Dampak Keluarga Broken Home Terhadap Motivasi Belajar Siswa dan Penanganannya - Bua, Dian Banga; Pandang, Abdullah; Saman, Abdul (Guidance : Jurnal Bimbingan dan Konseling, 2024)
This research aims to determine 1) the description of students learning motivation from broken home at SMK Kristen Harapan Rantepao, 2) the factors that students learning motivation is low , 3) the impact of broken home on students learning motivation, 4) handling problem learning motivation. This type of research is case study research with a qualitative approach. The instruments of this research are observation, interviews and documentation. Data collection uses interview and observation techniques. The results of the research show that: 1) Students from broken home families is still very low, this is shown in terms of student absenteeism who often do not attend without explanation, are late for school, do not do homework, do not complete assignments at school seriously, and are indifferent to learning 2) Factors that students cause a broken home are externally, namely parental divorce, economic conditions, egocentrism, and domestic violence, internal factors, namely low self-confidence, trauma, insecurity, 3) The impact of a broken home is feeling sad and embarrassed about the family situation, feeling depressed and traumatized, having difficulty controlling emotions, and decreased academic achievement. 4) The treatment handle broken home teenagers by providing counseling using a rational emotive behavior therapy approach.